Does Generation Z value and reward corporate social responsibility practices? - Narayanan, Sajith (Journal of marketing management, 2022)
Corporate activities vastly impact the environment and society, and people are increasingly becoming conscious of this. Generation Z (GenZ), an emerging customer segment globally, is particularly concerned about sustainability. Corporate social responsibility (CSR) initiatives assist businesses in meeting these expectations. Will purchase intention (PI), brand equity (BE), and willingness to pay (WTP) for these companies' brands rise as a result of their CSR initiatives? Will the effects of CSR's three dimensions-environmental, social, and economic - on these outcomes be different? To study this, a 4(CSR)* 2(brands) between-subjects factorial design experiment was conducted with 414 students in India using an incentive-based Becker-DeGroot-Marschak (BDM) procedure. Marketers and researchers will gain valuable insights into the effects of different dimensions of CSR on consumer behaviour from the findings of this study.